Aplicação distribuída de conversores buck-boost com quatro interruptores para minimizar efeitos de sombreamento e maximizar a extração de potência em módulos fotovoltaicos. - Côrtes, Luís Ricardo Cândido (2021)
There is a strong growth in the demand for installation of photovoltaic systems for distributed generation. This exponential increase in the last decade is realized by the need for energy relations with the concept of sustainability, water scarcity that raises the price of electricity production, increased government efforts that facilitate and improve financing conditions for the acquisition of photovoltaic structures. This work aims to present the distributed application of the four-switch Buck-Boost (FSBB) synchronous CC-CC converter, to maximize power extraction in photovoltaic modules and minimizing the shading effect. The photovoltaic modules suffered variations in solar irradiance and temperature, changing their current and voltage parameters, causing a significant loss in their supplied energy potential. The converters are connected to the outputs of the photovoltaic modules and the outputs of the converters are connected to mixed photovoltaic array, for different loads. This work elaborates control strategies using techniques, such as selective control, uncoupling your two modes of operation. Implementing the control strategies together there is maximum power point tracking algorithm (MPPT) to the FSBB converter so that it acts as a power source between photovoltaic module and load, capturing any and all produced power.